Windows Home Server Users Guide - Edney, Andrew (Apress : Imprint: Apress, 2007)
If you're searching for a practical and comprehensive guide to installing, configuring, and troubleshooting Microsofts Windows Home Server, look no further. Inside Windows Home Server User's Guide, you'll learn how to install, configure, and use Windows Home Server and understand how to connect to and manage different clients such as Windows XP, Windows Vista, Windows Media Center, and more. It's straightforward and easy-to-understand style will help you maximize all the benefits that Windows Home Server can bring. This guide includes the following: Step-by-step instructions for configurations Lots of troubleshooting tips Comprehensive coverage of different clients that can connect to, manage and be managed by Windows Home Server Many useful illustrations for a quick-to-learn approach Packed with handy hints, tips, and extensive walkthroughs to get you up and running as quickly and painlessly as possible, author Andrew Edney is your expert guide to help you get the most out of Windows Home Server.